2023
DOI: 10.21037/jgo-23-198
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-125b-5p derived from cancer-associated fibroblasts promotes the growth, migration, and invasion of pancreatic cancer cells by decreasing adenomatous polyposis coli (APC) expression

Abstract: Background: A significant desmoplastic response, particularly in the fibroblasts, is a characteristic of pancreatic ductal adenocarcinoma (PDAC). Increasing evidence has shown that cancer-associated fibroblasts (CAFs) assist tumor development, invasion, and metastasis in PDAC. However, CAFs-derived molecular determinants that regulate the molecular mechanisms of PDAC have not been fully characterized. Methods:The expression of microRNA 125b-5p (miR-125b-5p) in Pancreas Cancer (PC) tissue and para-cancerous nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Experimental studies have demonstrated that reducing the levels of miR-421 leads to a decrease in tumor growth that was initially stimulated by CAF-derived exosomes. Further emphasizing the role of CAFs in cancer progression, exosomal miR-125b-5p facilitates pancreatic cancer cell growth, migration, and invasion by suppressing the expression of the adenomatous polyposis coli (APC) gene, a known tumor suppressor [ 29 ]. This suppression leads to the activation of the Wnt signaling pathway.…”
Section: Relationship Between Cafs-derived Exosomes and Pancreatic Ca...mentioning
confidence: 99%
“…Experimental studies have demonstrated that reducing the levels of miR-421 leads to a decrease in tumor growth that was initially stimulated by CAF-derived exosomes. Further emphasizing the role of CAFs in cancer progression, exosomal miR-125b-5p facilitates pancreatic cancer cell growth, migration, and invasion by suppressing the expression of the adenomatous polyposis coli (APC) gene, a known tumor suppressor [ 29 ]. This suppression leads to the activation of the Wnt signaling pathway.…”
Section: Relationship Between Cafs-derived Exosomes and Pancreatic Ca...mentioning
confidence: 99%
“…Cancer-associated fibroblasts (CAFs) are the main cell type in the tumor stroma which play pivotal roles in ECM remodeling ( 14 - 17 ). Various bioactive molecules derived from CAFs such as growth factors, cytokines, and ECM-modifying enzymes, remodel the ECM environment, which not only provides mechanical support for tumor cells but also promotes tumor cell proliferation, metastasis, and drug resistance ( 15 , 17 - 19 ). However, the molecular mechanisms by which cancer cells influence pro-metastatic matrix remodeling are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%